Green advantage, integrated reporting, and carbon disclosure on firm value - Wijaya, Joshua Arta Iwan; Handoko, Jesica (Journal of Contemporary Accounting, 2025)
This study aims to examine the effect of green competitive advantage, integrated reporting, and carbon disclosure on firm value, with state ownership as a moderating variable. The object of this research is all manufacturing companies listed on the Indonesia Stock Exchange, spanning the period from 2021 to 2023. The population of manufacturing companies listed on the Indonesia Stock Exchange and the samples processed consisted of 438 companies, excluding outlier data from 18 companies. The analysis technique employs legitimacy and agency theory, examining the independent variable and the dependent variable in the presence of moderating variables and control variables, including firm size, leverage, and profitability. The results of this study indicate that a green competitive advantage has a positive but insignificant effect on firm value. In contrast, integrated reporting has a negative but insignificant effect on firm value. In contrast, carbon disclosure has a negative and significant effect on firm value. This study also examines moderation by creating interaction variables and assessing their impact on firm value as the dependent variable. There are three interaction variables: green competitive advantage with state ownership, integrated reporting with state ownership, and carbon disclosure with state ownership. The results of testing the effect of the interaction variables were found to be negatively insignificant, positively insignificant, and negatively significant. The discarded outlier data and measures used may have affected the results of this study.